LesionQuant for Assessment of MRI in Multiple Sclerosis—A Promising Supplement to the Visual Scan Inspection - Brune, Synne; Høgestøl, Einar A.; Cengija, Vanja; Berg-Hansen, Pål; Sowa, Piotr; Nygaard, Gro O.; Harbo, Hanne F.; Beyer, Mona K. (Frontiers in Neurology, 2020)
Background and goals: Magnetic resonance imaging (MRI) is an important tool for diagnosis and disease monitoring in Multiple Sclerosis(MS). Quantitative measurements of lesion volume, lesion count, distribution of lesions and brain atrophy have a potentially significant value for evaluating disease progression. We hypothesize that utilizing software designed for evaluating MRI data in MS will provide more accurate and detailed analyses compared to the visual neuro-radiological evaluation. Methods: A group of 56 MS patients (mean age 35 years, 70% females and 96% relapsing-remitting MS) was examined with brain MRI one and five years after diagnosis. The T1 and FLAIR brain MRI sequences for all patients were analysed using the LesionQuant (LQ) software. LQ data were compared with data from structured visual evaluations of the MRI scans performed by neuro-radiologists, and with data from other validated research methods for brain segmentation. Correlations with clinical tests like the timed 25-foot walk test (T25FT) were performed to explore additional value of LQ analyses. Results: Lesion count assessments by LQ and by the neuro-radiologist were significantly correlated one year (cor=0.92, p=2.2x10-16) and five years (cor=0.84, p=2.7x10-16) after diagnosis. Analyzes of the intra- and interrater variability also correlated significantly (cor =0.96, p<0.001, cor=0.97, p<0.001). LQ detected a reduction in whole brain percentile >10 in 10 patients across the time-points, whereas the neuro-radiologist assessment identified six of these. The neuro-radiologist additionally identified five patients with increased atrophy in the follow-up period, all of them displayed decreasing low whole brain percentiles (median 11, range 8-28) in the LQ analysis. Significant positive correlation was identified between lesion volume measured by LQ and test performance on the T25FT both at one year and five years after diagnosis. Conclusion: For the number of MS lesions we demonstrated strong correlations between the assessments done by LQ and the neuro-radiologist. LQ-analyses classified more patients to have brain atrophy than the visual neuro-radiological evaluation. In conclusion, LQ seems like a promising supplement to the evaluation performed by neuro-radiologists, providing an automated tool for evaluating lesions in MS patients and also detecting early signs of atrophy in both a longitudinal and cross-sectional setting.